Peningkatan Hasil Belajar Dengan Model PBL Pada Materi Sepuluh Perintah Allah di Kelas IV SDN 29 UPT SP IV - Anastasia Anastasia (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The learning outcomes of class IV students at SD Negeri 29 UPT SP IV for the 2022/2023 academic year are still low because they are only focused on activities such as listening, doing assignments, and relying completely on books resulting in less active learning. As a result, interaction between teachers and students and between students with each other becomes limited, causing learning to be not optimal and having a negative impact on achieving student learning outcomes. The material is delivered through the lecture method, teachers do not relate the material to real situations, and students are less active in the learning process. . This research aims to improve the learning achievement of class IV students and teacher performance in teaching the ten commandments of God as a guide to life by implementing the PBL model at SD Negeri 29 UPT SP IV. This research uses a classroom action research design consisting of two cycles. Each cycle consists of four steps: planning, implementing, observing, and reflecting. Data was collected through formative tests and observation and documentation. The results of research in cycle I showed that the average score reached 81.2 with a classical pass percentage of 70.59%. In cycle II, the average score increased to 89.00 with a classical pass percentage reaching 92.16%. The student attendance rate remained high in both cycles, namely 97.39%. Student involvement in learning also increased from 66.28% (high) in cycle I to 76.50% (very high) in cycle II. The teacher performance score increased from 82.25 (AB) in cycle I to 93.58 (A) in cycle II. In this series, it can be concluded that the application of the PBL model is effective in improving student learning achievement and teacher performance in teaching Catholic religious education material and morals about the ten commandments of God as a guide to life in class IV of SD Negeri 29 UPT SP IV